Rethinking the Concept of Politics and Politicians in a Transit State: Features of “the Political Labor Market” in Georgia - Chedia, Beka (HAPSc Policy Briefs Series, 2020)
The article examines the specificities of political activity in post-Soviet Georgia. It draws attention to how the profession of a politician is perceived in this country. What are the features of the recruitment process to the political elite? Why is the profession of a politician so attractive in Georgia and what contributes to the rapid growth in the number of political parties and political leaders? This article discusses criteria, conditions, and procedures for establishing political parties, as well as, the techniques that are used by politicians and parties in order to gain the attention of the country’s population.